The Use of Viral Vectors for Gene Therapy and Vaccination in Tuberculosis - Dulce Mata-Espinosa; Jacqueline V. Lara-Espinosa; Jorge Barrios-Payán; Rogelio Hernández-Pando (MDPI AG, 2023)
Tuberculosis (TB), an infection caused by Mycobacterium tuberculosis (Mtb), is one of the primary causes of death globally. The treatment of TB is long and based on several drugs, producing problems in compliance and toxicity, increasing Mtb resistance to first-line antibiotics that result in multidrug-resistant TB and extensively drug-resistant TB. Thus, the need for new anti-TB treatments has increased. Here, we review some model strategies to study gene therapy based on the administration of a recombinant adenovirus that encodes diverse cytokines, such as IFNγ, IL12, GM/CSF, OPN, TNFα, and antimicrobial peptides to enhance the protective immune response against Mtb. These models include a model of progressive pulmonary TB, a model of chronic infection similar to latent TB, and a murine model of pulmonary Mtb transmission to close contacts. We also review new vaccines that deliver Mtb antigens via particle- or virus-based vectors and trigger protective immune responses. The results obtained in this type of research suggest that this is an alternative therapy that has the potential to treat active TB as an adjuvant to conventional antibiotics and a promising preventive treatment for latent TB reactivation and Mtb transmission. Moreover, Ad vector vaccines are adequate for preventing infectious diseases, including TB.